Media Augmented Reality sebagai Solusi dalam Meningkatkan Pemahaman Siswa pada Materi Dimensi Tiga - Mulbar, Usman; Farhan, Muhammad (Alauddin Journal of Mathematics Education, 2024)
Difficulties in learning three-dimensional geometry often arise because students have difficulty imagining the shape of a geometric figure in real terms, while teachers face challenges in explaining the abstract concept. The low understanding of students towards this material is caused by the abstract nature of three-dimensional geometry and the ineffective use of learning media. Teachers tend to use simple media, such as whiteboards and simple sketches, without innovation to visualize concepts more concretely, such as distance or angles in geometric figures. Along with the development of technology, Android-based augmented reality has become a potential solution for visualizing three-dimensional objects interactively. This study aims to develop and test the effectiveness of augmented reality (AR)-based learning media on three-dimensional geometry material for grade XII students at SMA Negeri 15 Makassar. AR was developed using Unity and Vuforia, and integrated into the 2013 curriculum with the Plomp method as a development model. Testing was carried out to measure the validity, practicality, and effectiveness of this learning media. The results of the study showed that AR media is valid for learning, proven to be practical in classroom implementation, and effective in improving students' understanding of three-dimensional material. This AR media received positive responses from students and teachers, achieving a classical completion percentage of 85.19% on the student comprehension ability test, and meeting the effectiveness criteria based on student activities and responses during learning. The main obstacles involved student adaptation to AR technology and access to Android-based devices. This study concluded that AR media can be an innovative and effective solution in overcoming the difficulties of grade XII students at SMA Negeri 15 Makassar in understanding abstract concepts in three-dimensional geometry material.